Morphology of the pancreas of pacas (Cuniculus paca, Linnaeus, 1766) - Fiori, L. C. [UNESP]; Leal, L. M.; Sasahara, T. H. C.; Oliveira, F. S. [UNESP]; Simoes, L.; Martins, L. L.; Garcia Filho, S.; Machado, M. R. F. [UNESP] (Arquivo Brasileiro Medicina Veterinaria Zootecnia, 2019)
The present study aimed to describe the morphology of pacas (Cuniculus paca), a wild species belonging to the order Rodentia, found in tropical areas. The detailed anatomical knowledge of pacas is very important for conservation, experimental studies and commercialization because studies in literature about wild species are scarce. The pancreas of paca has lobes organized in diffuse branches at the macroscopic level and microscopically this organ has a loose connective tissue layer, originating septa that divide the gland into lobes composed of acini and pancreatic islets.
Keywords: anatomy; histology; pancreas; rodent